A simple chemical route for composition graded Cu(In, Ga)S2 thin film solar cells: multi-stage paste coating. Issue 125 (8th December 2015) - Park, Se Jin; An, Hee Sang; Kim, Ji Eun; Jeon, Hyo Sang; Yoon, Sam S.; Hwang, Yun Jeong; Kim, Jihyun; Kim, Dong-Wook; Min, Byoung Koun
Abstract : In order to realize the modulation of band-gap profile in low-cost and printable CuIn x Ga1− x S2 thin-film solar cells, a simple chemical route, namely a multi-stage paste coating method, was developed. Abstract : In order to realize the modulation of band-gap profile in low-cost and printable CuIn x Ga1− x S2 thin-film solar cells, a simple chemical route, namely a multi-stage paste coating method, was developed. In particular, with this method, multiple coatings with two precursor solution pastes with different compositions were applied. Elemental analysis techniques confirmed the formation of three different graded Ga distributions (front, back, and front-and-back gradient) throughout the absorber films depending on the coating sequence with two different pastes. The back gradient cell showed the largest power conversion efficiency of 7.29%, which was almost two times larger than those of the non-graded cells.